2014
DOI: 10.17656/sdj.10010
|View full text |Cite
|
Sign up to set email alerts
|

The use of maxillary first molar as forensic aid in racial and sexual dimorphism of Kurdish populaton in Sulaimani city

Abstract: Objectives: To find out the utility of using permanent maxillary first molar as a forensic tool for sex determination, and to compare tooth size for both side in the same sex in Kurdish people. Materials and Methods: The study sample comprised 120 casts of Kurdish peoples (67 females and 53 males) from Sulaimani city - Iraq, with age ranging from 13-33 years. The bucco-lingual (B-L) and mesio-distal (M-D) linear measurements of the maxillary first molars were calculated using digital vernier calipers. Percenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
2
1
Order By: Relevance
“…On the other hand, our results In contrast with another study that concluded The group of female revealed greater values were statistically significant for left MS width where left side MS width can be used to identify sex (6) .Also another study stated that The left MS width was the differentiation parameter (10) . Another study Concluded that comparison maxillary sinus volume between left and right sides were not statistically significant (11) .in addition to another study reported that The right MS has been reported to be greater than the left MS in both sexes (4) .…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, our results In contrast with another study that concluded The group of female revealed greater values were statistically significant for left MS width where left side MS width can be used to identify sex (6) .Also another study stated that The left MS width was the differentiation parameter (10) . Another study Concluded that comparison maxillary sinus volume between left and right sides were not statistically significant (11) .in addition to another study reported that The right MS has been reported to be greater than the left MS in both sexes (4) .…”
Section: Discussioncontrasting
confidence: 99%
“…Alternatively, the Lt side failed to exhibit significant sexual dimorphism (16) . Studies in other populations revealed inconsistent results, where significant grades of sexual dimorphism in the Rt first molar dimensions were found (17,18,20) . Asymmetry of the Rt and Lt MD diameters of maxillary first molars has been previously shown (20) .Whereas, Sonika et al, (21) identified greater sexual dimorphism on the Lt than on the Rt maxillary first molars.…”
Section: Discussionmentioning
confidence: 94%
“…9 It is recognized that the maxillary sinuses appear in most individuals up to the age of five, and due to the development of the permanent dentition until the age of 18-20, these sinus area undergoes changes in shape and volume. 10 An good imaging technique for evaluating the sino-nasal cavities is the CT scan. They provide a precise assessment of the paranasal sinuses, craniofacial bones, and the degree of sinus pneumatization.…”
Section: Discussionmentioning
confidence: 99%